Molecular-scale synchrotron X-ray investigations of solid-liquid interfaces in lithium-ion batteries - Cao, Chuntian; Steinrück, Hans-Georg (Reference Module in Chemistry, Molecular Sciences and Chemical Engineering)

Quantum 2-SAT on low dimensional systems is $\mathsf{QMA}_1$-complete: Direct embeddings and black-box simulation - Rudolph, Dorian; Gharibian, Sevag; Nagaj, Daniel (arXiv:2401.02368)
Despite the fundamental role the Quantum Satisfiability (QSAT) problem has played in quantum complexity theory, a central question remains open: At which local dimension does the complexity of QSAT transition from "easy" to "hard"? Here, we study QSAT with each constraint acting on a $k$-dimensional and $l$-dimensional qudit pair, denoted $(k,l)$-QSAT. Our first main result shows that, surprisingly, QSAT on qubits can remain $\mathsf{QMA}_1$-hard, in that $(2,5)$-QSAT is $\mathsf{QMA}_1$-complete. In contrast, $2$-SAT on qubits is well-known to be poly-time solvable [Bravyi, 2006]. Our second main result proves that $(3,d)$-QSAT on the 1D line with $d\in O(1)$ is also $\mathsf{QMA}_1$-hard. Finally, we initiate the study of 1D $(2,d)$-QSAT by giving a frustration-free 1D Hamiltonian with a unique, entangled ground state. Our first result uses a direct embedding, combining a novel clock construction with the 2D circuit-to-Hamiltonian construction of [Gosset, Nagaj, 2013]. Of note is a new simplified and analytic proof for the latter (as opposed to a partially numeric proof in [GN13]). This exploits Unitary Labelled Graphs [Bausch, Cubitt, Ozols, 2017] together with a new "Nullspace Connection Lemma", allowing us to break low energy analyses into small patches of projectors, and to improve the soundness analysis of [GN13] from $Ω(1/T^6)$ to $Ω(1/T^2)$, for $T$ the number of gates. Our second result goes via black-box reduction: Given an arbitrary 1D Hamiltonian $H$ on $d'$-dimensional qudits, we show how to embed it into an effective null-space of a 1D $(3,d)$-QSAT instance, for $d\in O(1)$. Our approach may be viewed as a weaker notion of "simulation" (à la [Bravyi, Hastings 2017], [Cubitt, Montanaro, Piddock 2018]). As far as we are aware, this gives the first "black-box simulation"-based $\mathsf{QMA}_1$-hardness result, i.e. for frustration-free Hamiltonians.

Guest Column: The 7 faces of quantum NP - Gharibian, Sevag (ACM SIGACT News)
When it comes to NP, its natural definition, its wide applicability across scientific disciplines, and its timeless relevance, the writing is on the wall: There can be only one. Quantum NP, on the other hand, is clearly the apple that fell far from the tree of NP. Two decades since the first definitions of quantum NP started rolling in, quantum complexity theorists face a stark reality: There's QMA, QCMA, QMA1, QMA(2), StoqMA, and NQP. In this article aimed at a general theoretical computer science audience, I survey these various definitions of quantum NP, their strengths and weaknesses, and why most of them, for better or worse, actually appear to fit naturally into the complexity zoo.

COVID-19 in Female and Male Athletes: Symptoms, Clinical Findings, Outcome, and Prolonged Exercise Intolerance—A Prospective, Observational, Multicenter Cohort Study (CoSmo-S) - Widmann, Manuel; Gaidai, Roman; Schubert, Isabel; Grummt, Maximilian; Bensen, Lieselotte; Kerling, Arno; Quermann, Anne; Zacher, Jonas; Vollrath, Shirin; Bizjak, Daniel Alexander; Beckendorf, Claudia; Egger, Florian; et al. (Sports Medicine)
Abstract Background An infection with SARS-CoV-2 can lead to a variety of symptoms and complications, which can impair athletic activity. Objective We aimed to assess the clinical symptom patterns, diagnostic findings, and the extent of impairment in sport practice in a large cohort of athletes infected with SARS-CoV-2, both initially after infection and at follow-up. Additionally, we investigated whether baseline factors that may contribute to reduced exercise tolerance at follow-up can be identified. Methods In this prospective, observational, multicenter study, we recruited German COVID elite-athletes (cEAs, n = 444) and COVID non-elite athletes (cNEAs, n = 481) who tested positive for SARS-CoV-2 by PCR (polymerase chain reaction test). Athletes from the federal squad with no evidence of SARS-CoV-2 infection served as healthy controls (EAcon, n = 501). Questionnaires were used to assess load and duration of infectious symptoms, other complaints, exercise tolerance, and duration of training interruption at baseline and at follow-up 6 months after baseline. Diagnostic tests conducted at baseline included resting and exercise electrocardiogram (ECG), echocardiography, spirometry, and blood analyses. Results Most acute and infection-related symptoms and other complaints were more prevalent in cNEA than in cEAs. Compared to cEAs, EAcon had a low symptom load. In cNEAs, female athletes had a higher prevalence of complaints such as palpitations, dizziness, chest pain, myalgia, sleeping disturbances, mood swings, and concentration problems compared to male athletes ( p < 0.05). Until follow-up, leading symptoms were drop in performance, concentration problems, and dyspnea on exertion. Female athletes had significantly higher prevalence for symptoms until follow-up compared to male. Pathological findings in ECG, echocardiography, and spirometry, attributed to SARS-CoV-2 infection, were rare in infected athletes. Most athletes reported a training interruption between 2 and 4 weeks (cNEAs: 52.9%, cEAs: 52.4%), while more cNEAs (27.1%) compared to cEAs (5.1%) had a training interruption lasting more than 4 weeks ( p < 0.001). At follow-up, 13.8% of cNEAs and 9.9% of cEAs ( p = 0.24) reported their current exercise tolerance to be under 70% compared to pre-infection state. A persistent loss of exercise tolerance at follow-up was associated with persistent complaints at baseline, female sex, a longer break in training, and age > 38 years. Periodical dichotomization of the data set showed a higher prevalence of infectious symptoms such as cough, sore throat, and coryza in the second phase of the pandemic, while a number of neuropsychiatric symptoms as well as dyspnea on exertion were less frequent in this period. Conclusions Compared to recreational athletes, elite athletes seem to be at lower risk of being or remaining symptomatic after SARS-CoV-2 infection. It remains to be determined whether persistent complaints after SARS-CoV-2 infection without evidence of accompanying organ damage may have a negative impact on further health and career in athletes. Identifying risk factors for an extended recovery period such as female sex and ongoing neuropsychological symptoms could help to identify athletes, who may require a more cautious approach to rebuilding their training regimen. Trial Registration Number DRKS00023717; 06.15.2021—retrospectively registered.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Effect of DNA Origami Nanostructures on Bacterial Growth - Garcia-Diosa, Jaime Andres; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
DNA origami nanostructures are a powerful tool in biomedicine and can be used to combat drug‐resistant bacterial infections. However, the effect of unmodified DNA origami nanostructures on bacteria is yet to be elucidated. With the aim to obtain a better understanding of this phenomenon, the effect of three DNA origami shapes, i.e., DNA origami triangles, six‐helix bundles (6HBs), and 24‐helix bundles (24HBs), on the growth of Gram‐negative Escherichia coli and Gram‐positive Bacillus subtilis is investigated. These results reveal that while triangles and 24HBs can be used as a source of nutrients by E. coli and thereby promote population growth, their effect is much smaller than that of genomic single‐ and double‐stranded DNA. However, no effect on E. coli population growth is observed for the 6HBs. On the other hand, B. subtilis does not show any significant changes in population growth when cultured with the different DNA origami shapes or genomic DNA. The detailed effect of DNA origami nanostructures on bacterial growth thus depends on the competence signals and uptake mechanism of each bacterial species, as well as the DNA origami shape. This should be considered in the development of antimicrobial DNA origami nanostructures.
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

A note on the convergence of deterministic gradient sampling in nonsmooth optimization - Gebken, Bennet (Computational Optimization and Applications)
Abstract Approximation of subdifferentials is one of the main tasks when computing descent directions for nonsmooth optimization problems. In this article, we propose a bisection method for weakly lower semismooth functions which is able to compute new subgradients that improve a given approximation in case a direction with insufficient descent was computed. Combined with a recently proposed deterministic gradient sampling approach, this yields a deterministic and provably convergent way to approximate subdifferentials for computing descent directions.
Keywords: Applied Mathematics; Computational Mathematics; Control and Optimization

Leibniz’s Influence on 19th Century Logic - Peckhaus, Volker (The Stanford Encyclopedia of Philosophy, first published Sep 4, 2009, substantive revision Feb 2, 2024)

Fast Multiobjective Gradient Methods with Nesterov Acceleration via Inertial Gradient-Like Systems - Sonntag, Konstantin; Peitz, Sebastian (Journal of Optimization Theory and Applications)
We derive efficient algorithms to compute weakly Pareto optimal solutions for smooth, convex and unconstrained multiobjective optimization problems in general Hilbert spaces. To this end, we define a novel inertial gradient-like dynamical system in the multiobjective setting, which trajectories converge weakly to Pareto optimal solutions. Discretization of this system yields an inertial multiobjective algorithm which generates sequences that converge weakly to Pareto optimal solutions. We employ Nesterov acceleration to define an algorithm with an improved convergence rate compared to the plain multiobjective steepest descent method (Algorithm 1). A further improvement in terms of efficiency is achieved by avoiding the solution of a quadratic subproblem to compute a common step direction for all objective functions, which is usually required in first-order methods. Using a different discretization of our inertial gradient-like dynamical system, we obtain an accelerated multiobjective gradient method that does not require the solution of a subproblem in each step (Algorithm 2). While this algorithm does not converge in general, it yields good results on test problems while being faster than standard steepest descent.

Herstellung und Charakterisierung von Wood-Plastic-Composites (WPC) mit einer Matrix aus thermoplastischen Polyurethanen zur Erzeugung einer Holz-WPC-Verbundstruktur - Richters, Maximilian

Herausforderungen in der inklusiven Mädchenarbeit: Begleitforschung der „Inklusiven anonymen Zuflucht“ des Mädchenhaus Bielefeld e.V. - Richter, Susanne (Inklusiver Kinderschutz – Anforderungen, Herausforderungen, Perspektiven)

ADMM-TGV image restoration for scientific applications with unbiased parameter choice - Zietlow, Christian; Lindner, Jörg (Numerical Algorithms)

"Das Berufsfeldpraktikum empfinde ich als nicht notwendig im Studium" - Evaluationsergebnisse zum Berufsfeldpraktikum aus Sicht von Lehramtsstudierenden - Meier, Jana; Vogelsang, Christoph; Rotärmel, Tanja (Das Berufsfeldpraktikum als Professionalisierungselement. Grundlagen, Konzepte, Beispiele für das Lehramtsstudium)

Insights into the First Multi-Transition-Metal Containing Ruddlesden Popper-Type Cathode for all-solid-state Fluoride Ion Batteries - Vanita, Vanita; Waidha, Aamir Iqbal; Vasala, Sami; Puphal, Pascal; Schoch, Roland; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver (Journal of Materials Chemistry A)
Promising cathode materials for fluoride-ion batteries (FIBs) are 3d transition metal containing oxides with Ruddlesden-Popper-type structure. So far, multi-elemental compositions were not investigated, but could alternate electrochemical performance similar to what has been found for cathode materials for lithium-ion batteries. Within this study, we investigate RP type La2Ni0.75Co0.25O4.08 as an intercalation-based active cathode material for all-solid-state FIBs. We determine the structural changes of La2Ni0.75Co0.25O4.08 during fluoride intercalation / de-intercalation by ex-situ X-ray diffraction, which showed that F- insertion leads to transformation of the parent phase to three different phases. Changes in Ni and Co oxidation states and coordination environment were examined by X-ray absorption spectroscopy and magnetic measurements in order to understand the complex reaction behaviour of the phases in detail, showing that the two transition metals behave differently in the charging and discharging process. Under optimized operating conditions, a cycle life of 120 cycles at a critical cut-off capacity of 40 mAh g-1 against Pb/PbF2 was obtained, which is one of the highest observed for intercalation electrode materials in FIBs so far. The average Coulombic efficiencies ranged from 85% to 90%. Thus, La2Ni0.75Co0.25O4.08 could be a promising candidate for cycling-stable high-energy cathode materials for all-solid-state FIBs
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

WeGA-WebApp release 4.9.0 - Stadler, Peter; Schmidt, Jakob; Zheng, Xianghua; Ried, Dennis; Richts, Kristina; Schreiter, Solveig; Jakob, Charlene
WeGA-WebApp release 4.9.0 Main features replace external Beacon service #451 update csLink to version v2 #450 Changelog A detailed changelog can be found at https://github.com/Edirom/WeGA-WebApp/wiki/Changelog Full Changelog: v4.8.1...v4.9.0 License This work is available under dual license: BSD 2-Clause and Creative Commons Attribution 4.0 International License (CC BY 4.0)

A Comparative Kinetic and Computational Investigation of the Carbon‐Sulfur Cross Coupling of Potassium Thioacetate and 2‐Bromo Thiophene Using Palladium/Bisphosphine Complexes - Peschtrich, Sebastian; Schoch, Roland; Kuckling, Dirk; Paradies, Jan (European Journal of Organic Chemistry)
Abstract We conducted an investigation into the palladium‐catalyzed carbon‐sulfur cross‐coupling reaction involving a 2‐bromothiophene derivative and potassium thioacetate as a substitute for hydrogen sulfide. This investigation utilized kinetic and computational methods. We synthesized two palladium complexes supported by the bisphosphane ligands bis(diphenylphosphino)ferrocene (DPPF) and bis(diisopropylphosphino)ferrocene (D i PPF), as well as their tentative intermediates in the catalytic cycle. Reaction rates were measured and then compared to computational predictions.
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Synthesis of Ferrocenyl Boranes and their Application as Lewis Acids in Epoxide Rearrangements - Köring, Laura; Birenheide, Bernhard; Krämer, Felix; Wenzel, Jonas O.; Schoch, Roland; Brehm, Martin; Breher, Frank; Paradies, Jan (European Journal of Inorganic Chemistry)
A series of substituted ferrocenyl boron derivatives was synthesized. The oxidation of the ferrocenyl unit resulted in a significant increase of the boron‐centered Lewis acidity. The neutral and cationic Lewis acids were characterized by NMR‐spectroscopy, crystal structure analysis and by computational methods. The new Lewis acids were then applied in the Meinwald rearrangement of epoxides, predominantly furnishing aldehydes as the kinetic products.
Keywords: Inorganic Chemistry

Simulationsgestützte Bestimmung und Optimierung der Mischgüte in der Einschneckenextrusion - Frank, Maximilian

Alexandra Treder (Universität Paderborn) rezensiert: Döll, Marion & Michalak, Magdalena (2023): Deutsch als Zweitsprache und inklusive Bildung. [Deutsch als Zweitsprache – Positionen, Perspektiven, Potenziale, Bd. 3]. Münster: Waxmann, 142 Seiten. ISBN 978-3-8309-4711-0. - Treder, Alexandra (Forschungsportal für Spracherwerb und Migration (daz-portal))

Anisotropic Mechanical and Microstructural Properties of a Ti-6Al-7Nb Alloy for Biomedical Applications Manufactured via Laser Powder Bed Fusion - Milaege, Dennis; Eschemann, Niklas; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
Through tailoring the geometry and design of biomaterials, additive manufacturing is revolutionizing the production of metallic patient-specific implants, e.g., the Ti-6Al-7Nb alloy. Unfortunately, studies investigating this alloy showed that additively produced samples exhibit anisotropic microstructures. This anisotropy compromises the mechanical properties and complicates the loading state in the implant. Moreover, the minimum requirements as specified per designated standards such as ISO 5832-11 are not met. The remedy to this problem is performing a conventional heat treatment. As this route requires energy, infrastructure, labor, and expertise, which in turn mean time and money, many of the additive manufacturing benefits are negated. Thus, the goal of this work was to achieve better isotropy by applying only adapted additive manufacturing process parameters, specifically focusing on the build orientations. In this work, samples orientated in 90°, 45°, and 0° directions relative to the building platform were manufactured and tested. These tests included mechanical (tensile and fatigue tests) as well as microstructural analyses (SEM and EBSD). Subsequently, the results of these tests such as fractography were correlated with the acquired mechanical properties. These showed that 90°-aligned samples performed best under fatigue load and that all requirements specified by the standard regarding monotonic load were met.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Edge-Connectivity and Pairwise Disjoint Perfect Matchings in Regular Graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (Combinatorica)
For 0 ≤ t ≤ r let m(t, r) be the maximum number s such that every t-edge-connected r-graph has s pairwise disjoint perfect matchings. There are only a few values of m(t, r) known, for instance m(3, 3) = m(4, r) = 1, and m(t, r) ≤ r − 2 for all t = 5, and m(t, r) ≤ r − 3 if r is even. We prove that m(2l, r) ≤ 3l − 6 for every l ≥ 3 and r ≥ 2l.
Keywords: Computational Mathematics; Discrete Mathematics and Combinatorics

Electrochemical Removal of HF from Carbonate-based LiPF6-containing Li-ion Battery Electrolytes - Ge, Xiaokun; Huck, Marten; Kuhlmann, Andreas; Tiemann, Michael; Weinberger, Christian; Xu, Xiaodan; Zhao, Zhenyu; Steinrueck, Hans-Georg (Journal of The Electrochemical Society)
Due to the hydrolytic instability of LiPF6 in carbonate-based solvents, HF is a typical impurity in Li-ion battery electrolytes. HF significantly influences the performance of Li-ion batteries, for example by impacting the formation of the solid electrolyte interphase at the anode and by affecting transition metal dissolution at the cathode. Additionally, HF complicates studying fundamental interfacial electrochemistry of Li-ion battery electrolytes, such as direct anion reduction, because it is electrocatalytically relatively unstable, resulting in LiF passivation layers. Methods to selectively remove ppm levels of HF from LiPF6-containing carbonate-based electrolytes are limited. We introduce and benchmark a simple yet efficient electrochemical in situ method to selectively remove ppm amounts of HF from LiPF6-containing carbonate-based electrolytes. The basic idea is the application of a suitable potential to a high surface-area metallic electrode upon which only HF reacts (electrocatalytically) while all other electrolyte components are unaffected under the respective conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Das Schreiben im Geschichtsunterricht der Sekundarstufe I unter Berücksichtigung der Bedingungen der Migrationsgesellschaft - Altun, Tülay; Günther, Katrin (Mehrsprachigkeit in der Schule. Sprachbildung im und durch Sachunterricht)

Herstellung und Charakterisierung von Wood-Plastic-Composites (WPC) mit einer Matrix aus thermoplastischen Polyurethanen zur Erzeugung einer Holz-WPC-Verbundstruktur - Richters, Maximilian

Doing language im Deutschunterricht. Eine Analyse sprachbezogener Adressierungen in diskursiver Praxis - Büttner, Denise
Die Studie leistet einen empirisch-rekonstruktiven Beitrag zu einer machtkritisch ausgerichteten Fachdidaktik. Sie fokussiert den Deutschunterricht und die darin stattfindenden Interaktionen als diskursive Praxis, in der ein spezifisches Wissen in, über und angesichts von Sprache relevant gemacht wird. Für Subjektivierung ist jenes Wissen hochgradig wirkmächtig und bleibt den Akteur*innen im Prozess der schulischen Enkulturation doch größtenteils unbewusst. Darin liegt ein hohes Potential für die institutionelle (Re-)Produktion von Linguizismus.Vor diesem Hintergrund eröffnet die Studie einen Blick auf sprachbezogene Adressierungen, die in charakteristischer Weise vom Fach selbst ausgehen. Sie werden in (fach)didaktischen und pädagogischen Programmatiken breit kommuniziert und zeichnen sich bis auf die Ebene unterrichtlicher Praktiken ab. Um das Zusammenspiel von fachspezifischer Adressierung und Praktiken des ‚doing language‘ möglichst eng aufeinander beziehen und in rekonstruktionslogisch plausibilisierte Zusammenhänge bringen zu können, liegt der Arbeit ein wissenssoziologisch-diskursanalytischer Ansatz zugrunde.
Keywords: Diskursanalyse; Machtkritik; Sprache und Bildung; Rekonstruktive Unterrichtsforschung; Subjektivierung; Fachdidaktik

Pillar[5]arene-based dually crosslinked supramolecular gel as a sensor for the detection of adiponitrile - Rodin, Maksim; Helle, David; Kuckling, Dirk (Polymer Chemistry)
An SPR-based dually crosslinked gel sensor for adiponitrile bearing pillar[5]arene responsive sites with a low limit of detection was developed.
Keywords: Organic Chemistry; Polymers and Plastics; Biochemistry; Bioengineering

A critical exponent in a quasilinear Keller–Segel system with arbitrarily fast decaying diffusivities accounting for volume-filling effects - Stinner, Christian; Winkler, Michael (Journal of Evolution Equations)
Abstract The quasilinear Keller–Segel system $$\begin{aligned} \left\{ \begin{array}{l} u_t=\nabla \cdot (D(u)\nabla u) - \nabla \cdot (S(u)\nabla v), \\ v_t=\Delta v-v+u, \end{array}\right. \end{aligned}$$ u t = ∇ · ( D ( u ) ∇ u ) - ∇ · ( S ( u ) ∇ v ) , v t = Δ v - v + u , endowed with homogeneous Neumann boundary conditions is considered in a bounded domain $$\Omega \subset {\mathbb {R}}^n$$ Ω ⊂ R n , $$n \ge 3$$ n ≥ 3 , with smooth boundary for sufficiently regular functions D and S satisfying $$D>0$$ D > 0 on $$[0,\infty )$$ [ 0 , ∞ ) , $$S>0$$ S > 0 on $$(0,\infty )$$ ( 0 , ∞ ) and $$S(0)=0$$ S ( 0 ) = 0 . On the one hand, it is shown that if $$\frac{S}{D}$$ S D satisfies the subcritical growth condition $$\begin{aligned} \frac{S(s)}{D(s)} \le C s^\alpha \qquad \text{ for } \text{ all } s\ge 1 \qquad \text{ with } \text{ some } \alpha < \frac{2}{n} \end{aligned}$$ S ( s ) D ( s ) ≤ C s α for all s ≥ 1 with some α < 2 n and $$C>0$$ C > 0 , then for any sufficiently regular initial data there exists a global weak energy solution such that $${ \mathrm{{ess}}} \sup _{t>0} \Vert u(t) \Vert _{L^p(\Omega )}<\infty $$ ess sup t > 0 ‖ u ( t ) ‖ L p ( Ω ) < ∞ for some $$p > \frac{2n}{n+2}$$ p > 2 n n + 2 . On the other hand, if $$\frac{S}{D}$$ S D satisfies the supercritical growth condition $$\begin{aligned} \frac{S(s)}{D(s)} \ge c s^\alpha \qquad \text{ for } \text{ all } s\ge 1 \qquad \text{ with } \text{ some } \alpha > \frac{2}{n} \end{aligned}$$ S ( s ) D ( s ) ≥ c s α for all s ≥ 1 with some α > 2 n and $$c>0$$ c > 0 , then the nonexistence of a global weak energy solution having the boundedness property stated above is shown for some initial data in the radial setting. This establishes some criticality of the value $$\alpha = \frac{2}{n}$$ α = 2 n for $$n \ge 3$$ n ≥ 3 , without any additional assumption on the behavior of D ( s ) as $$s \rightarrow \infty $$ s → ∞ , in particular without requiring any algebraic lower bound for D . When applied to the Keller–Segel system with volume-filling effect for probability distribution functions of the type $$Q(s) = \exp (-s^\beta )$$ Q ( s ) = exp ( - s β ) , $$s \ge 0$$ s ≥ 0 , for global solvability the exponent $$\beta = \frac{n-2}{n}$$ β = n - 2 n is seen to be critical.
Keywords: Mathematics (miscellaneous)

Rezension zu Anna-Victoria Bognár: Der Architekt in der Frühen Neuzeit. Ausbildung, Karrierewege, Berufsfelder (=Höfische Kultur interdisziplinär. Schriften und Materialien des Rudolfstädter Arbeitskreises. 2). Heidelberg 2020. - Voß, Fabian (Mitteilungen des Instituts für Europäische Kulturgeschichte)

Characterizing Microheterogeneity in Liquid Mixtures via Local Density Fluctuations - Lass, Michael; Kenter, Tobias; Plessl, Christian; Brehm, Martin (Entropy)
We present a novel approach to characterize and quantify microheterogeneity and microphase separation in computer simulations of complex liquid mixtures. Our post-processing method is based on local density fluctuations of the different constituents in sampling spheres of varying size. It can be easily applied to both molecular dynamics (MD) and Monte Carlo (MC) simulations, including periodic boundary conditions. Multidimensional correlation of the density distributions yields a clear picture of the domain formation due to the subtle balance of different interactions. We apply our approach to the example of force field molecular dynamics simulations of imidazolium-based ionic liquids with different side chain lengths at different temperatures, namely 1-ethyl-3-methylimidazolium chloride, 1-hexyl-3-methylimidazolium chloride, and 1-decyl-3-methylimidazolium chloride, which are known to form distinct liquid domains. We put the results into the context of existing microheterogeneity analyses and demonstrate the advantages and sensitivity of our novel method. Furthermore, we show how to estimate the configuration entropy from our analysis, and we investigate voids in the system. The analysis has been implemented into our program package TRAVIS and is thus available as free software.

Klopstocks lyrisches Spätwerk. Perspektivwechsel und Blickerweiterungen - Elit, Stefan („Wer wird nicht einen Klopstock loben?“ Friedrich Gottlieb Klopstocks poetische Innovationen und ihre produktive Rezeption)

Lines in the Sand - Langer, Svenja

Imagining and Governing Artificial Intelligence – the Ordoliberal Way: An Analysis of the National Strategy ‘AI Made in Germany’ - Hälterlein, Jens (AI & Society)

„Wir wollen mitreden!“ – Entwicklung und Validierung von Skalen zur Erfassung motivationaler Regulation bei der Teilnahme an Befragungen zur Evaluation des Studiums (SMR-Eval) - Koppenborg, Markus; Klingsieck, Katrin B. (Zeitschrift für Pädagogische Psychologie)
Zusammenfassung: Für die Evaluation und Qualitätsentwicklung von Studium und Lehre werden häufig quantitative Befragungen von Studenten eingesetzt. Jedoch ist häufig unklar, aus welcher Motivation Studenten an den Befragungen teilnehmen und inwieweit unterschiedliche motivationale Regulationsstile mit dem Antwortverhalten im Fragebogen zusammenhängen. Ausgehend von der Selbstbestimmungstheorie der Motivation nach Deci und Ryan stellt der Beitrag die Entwicklung der Skalen zur motivationalen Regulation bei Befragungen zur Evaluation (SMR-Eval) vor. Studie 1 zeigt die fünffaktorielle Struktur des Instruments. Studie 2 weist auf eine starke Messinvarianz bezüglich Geschlecht, Abschlussziel und Fakultät hin. Korrelationen mit Drittvariablen belegen die konvergente Validität der fünf Subskalen. In Studie 3 werden latente Profilanalysen über die fünf Regulationsstile berechnet. Die Ergebnisse zeigen vier Profile, welche sich inhaltlich plausibel im Antwortverhalten der Befragten unterscheiden und damit Hinweise auf die Kriteriumsvalidität der Skalen geben. Diskutiert werden theoretische und praktische Implikationen für Evaluationsvorhaben an Hochschulen sowie Übertragungsmöglichkeiten auf andere Evaluationsgegenstände.
Keywords: Developmental and Educational Psychology

Cold denaturation of DNA origami nanostructures - Dornbusch, Daniel; Hanke, Marcel; Tomm, Emilia; Kielar, Charlotte; Grundmeier, Guido; Keller, Adrian; Fahmy, Karim (Chemical Communications)
The coupling of structural transitions to heat capacity changes leads to destabilization of macromolecules at both, elevated and lowered temperatures. DNA origami not only exhibit this property but also provide...
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Playing games with QCA: Measuring the explanatory power of single conditions with the Banzhaf index - Haake, Claus-Jochen; Schneider, Martin (Journal of International Management)
Qualitative comparative analysis (QCA) enables researchers in international management to better understand how the impact of a single explanatory factor depends on the context of other factors. But the analytical toolbox of QCA does not include a parameter for the explanatory power of a single explanatory factor or “condition”. In this paper, we therefore reinterpret the Banzhaf power index, originally developed in cooperative game theory, to establish a goodness-of-fit parameter in QCA. The relative Banzhaf index we suggest measures the explanatory power of one condition averaged across all sufficient combinations of conditions. The paper argues that the index is especially informative in three situations that are all salient in international management and call for a context-sensitive analysis of single conditions, namely substantial limited diversity in the data, the emergence of strong INUS conditions in the analysis, and theorizing with contingency factors. The paper derives the properties of the relative Banzhaf index in QCA, demonstrates how the index can be computed easily from a rudimentary truth table, and explores its insights by revisiting selected papers in international management that apply fuzzy-set QCA. It finally suggests a three-step procedure for utilizing the relative Banzhaf index when the causal structure involves both contingency effects and configurational causation.
Keywords: Qualitative comparative analysis; Banzhaf power index; causality; explanatory power

The association between dairy intake in adolescents with inflammation and risk markers of type 2 diabetes during young adulthood – results of the DONALD study - Hohoff, E; Jankovic, N; Perrar, I; Schnermann, ME; Herder, C; Nöthlings, U; Libuda, Lars; Alexy, U (Public Health Nutrition)
ABSTRACT OBJECTIVE: The aim of this analysis was to investigate whether habitual intake of total dairy (TD) or different dairy types (liquid, solid, fermented, not-fermented, low-fat, high-fat, low-sugar and high-sugar dairy) during adolescence is associated with biomarkers of low-grade inflammation as well as risk factors of type 2 diabetes in young adulthood. DESIGN: Multivariable linear regression analyses were used to investigate prospective associations between estimated TD intake as well as intake of different types of dairy and a pro-inflammatory score, based on hsCRP, IL-6, IL-18, leptin and adiponectin, and insulin resistance assessed as HOMA2-IR in an open cohort study. SETTING: Dortmund, Germany PARTICIPANTS: Data from participants (n=375) of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were included, for whom at least two 3-day weighed dietary records during adolescence (median age: 11 years) and one blood sample in young adulthood (>18 years) were available. RESULTS: There was no statistically significant association between TD intake or intake of any dairy type and the pro-inflammatory score (all p>0.05). TD intake as well as each dairy type intake and insulin resistance also showed no association (all p>0.05). CONCLUSIONS: The habitual intake of dairy or individual types of dairy during adolescence does not seem to have a major impact on low-grade systemic inflammation and insulin resistance in the long term. There was no indication regarding a restriction of dairy intake for healthy children and adolescents in terms of diabetes risk reduction.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

Noctua 2 Supercomputer - Bauer, Carsten; Kenter, Tobias; Lass, Michael; Mazur, Lukas; Meyer, Marius; Nitsche, Holger; Riebler, Heinrich; Schade, Robert; Schwarz, Michael; Winnwa, Nils; Wiens, Alex; Wu, Xin; et al. (Journal of large-scale research facilities)
Noctua 2 is a supercomputer operated at the Paderborn Center for Parallel Computing (PC2) at Paderborn University in Germany. Noctua 2 was inaugurated in 2022 and is an Atos BullSequana XH2000 system. It consists mainly of three node types: 1) CPU Compute nodes with AMD EPYC processors in different main memory configurations, 2) GPU nodes with NVIDIA A100 GPUs, and 3) FPGA nodes with Xilinx Alveo U280 and Intel Stratix 10 FPGA cards. While CPUs and GPUs are known off-the-shelf components in HPC systems, the operation of a large number of FPGA cards from different vendors and a dedicated FPGA-to-FPGA network are unique characteristics of Noctua 2. This paper describes in detail the overall setup of Noctua 2 and gives insights into the operation of the cluster from a hardware, software and facility perspective.
Keywords: Noctua 2; Supercomputer; FPGA; PC2; Paderborn Center for Parallel Computing

Personalizing real‐world problems: Posing own problems increases self‐efficacy expectations, intrinsic value, attainment value, and utility value - Schoenherr, Johanna (British Journal of Educational Psychology)
Abstract Background Real‐world problems are important in math instruction, but they do not necessarily trigger students' task motivation. Personalizing real‐world problems by (1) matching problems to students' shared living environment (context personalization) and (2) asking students to pose their own problems (active personalization) might be two interventions to increase students' task motivation. Aim In the current study, we investigated the effects of context personalization and active personalization on students' self‐efficacy expectations, intrinsic value, attainment value, utility value, and cost. Sample The participants were 28 fifth‐ and sixth‐grade students who voluntarily took part in a six‐month afterschool program in which they posed problems with the aim of creating a math walk in their hometown. Method Using a within‐subjects design, at the end of the afterschool program, the students rated their self‐efficacy expectations and task values for four self‐developed problems associated with their hometown, four peer‐developed problems associated with their hometown, and four instructor‐provided problems associated with unfamiliar locations. Results Students reported higher self‐efficacy expectations, intrinsic value, attainment value, and utility value for active‐personalized than non‐personalized problems. To a lesser extent, context personalization promoted intrinsic value and attainment value. No effect was found for cost. Conclusions Active personalization (i.e. asking students to pose their own real‐world problems) is suited to enhance students' task motivation, specifically their self‐efficacy expectations, intrinsic value, attainment value, and utility value. Context personalization still boosts students' intrinsic value and attainment value. Implementation in classroom instruction is discussed.
Keywords: Developmental and Educational Psychology; Education

Detection and Characterization of Hydride Ligands in Copper Complexes by Hard X‐ray Spectroscopy - Fritsch, Lorena; Rehsies, Pia; Barakat, Wael; Estes, Deven P.; Bauer, Matthias (Chemistry – A European Journal)
Transition metal complexes, particularly copper hydrides, play an important role in various catalytic processes and molecular inorganic chemistry. This study employs synchrotron hard X‐ray spectroscopy to gain insights into the geometric and electronic properties of copper hydrides as potential catalysts for CO2 hydrogenation. The potential of high energy resolution X‐ray absorption near‐edge structure (HERFD‐XANES) and valence‐to‐core X‐ray emission (VtC‐XES) is demonstrated with measurement on Stryker's reagent (Cu6H6) and [Cu3(μ3‐H)(dpmppe)2](PF6)2 (Cu3H), alongside a non‐hydride copper compound (Cu‐I). The XANES analysis reveals that coordination geometries strongly influence the spectra, providing only indirect details about hydride coordination. The VtC‐XES analysis exhibits a distinct signal around 8975 eV, offering a diagnostic tool to identify hydride ligands. Theoretical calculations support and extend these findings by comparing hydride‐containing complexes with their hydride‐free counterparts.

Temperedness of locally symmetric spaces: The product case - Weich, Tobias; Wolf, Lasse Lennart (Geom Dedicata)
Let $X=X_1× X_2$ be a product of two rank one symmetric spaces of non-compact type and $Γ$ a torsion-free discrete subgroup in $G_1× G_2$. We show that the spectrum of $Γ \backslash X$ is related to the asymptotic growth of $Γ$ in the two direction defined by the two factors. We obtain that $L^2(Γ \backslash G)$ is tempered for large class of $Γ$.

Polyhedral bounds on the joint spectrum and temperedness of locally symmetric spaces - Lutsko, Christopher; Weich, Tobias; Wolf, Lasse Lennart (arXiv:2402.02530)
Given a real semisimple connected Lie group $G$ and a discrete torsion-free subgroup $Γ < G$ we prove a precise connection between growth rates of the group $Γ$, polyhedral bounds on the joint spectrum of the ring of invariant differential operators, and the decay of matrix coefficients. In particular, this allows us to completely characterize temperedness of $L^2(Γ\backslash G)$ in this general setting.

“Der Draht ist gut, hält uns ab vom dummen Leben“. Ironisierung als kommunikativer Versuch des Umgangs mit Entwertungs- und Gewalterfahrungen durch jüdische Textproduzenten im Getto Litzmannstadt - Markewitz, Friedrich (Invective Discourse)
Immediately after the National Socialist seizure of power, a comprehen-sive social, legal and ultimately existential exclusion of Jewish people began. The disturbing perception of the break-up of previous understandings of the world was intensified against the background of the acts of annihilation by the National Socialists. Countering this in a communicative form became an often agonizing challenge for Jewish speakers, but also a necessary need. This paper will focus on a communicative phenomenon that has been little researched in linguistics so far: The use of irony to counter experiences of devaluation and violence. By eval-uating ironic utterances in textual communications of the Litzmannstadt ghetto, the criticism of elements of National Socialist ideology will be tentatively made understandable, as well as the experiences of violence within the ghetto.

Haus oder Schule? oder Haus und Schule? Zur kulturell-gesellschaftlichen Bedeutung der historischen Textsorte 'Schulprogramm' hinsichtlich der Konstitution, Festigung wie Abgrenzung des Erziehungssystems im 19. Jahrhundert - Markewitz, Friedrich (Textsorten in Sprach-, Kultur- und Sozialgeschichte)

Ironie - Markewitz, Friedrich
Ironie lässt sich als uneigentliches Kommunikationsmittel beschreiben, mit dem etwas anderes zum Ausdruck gebracht wird, als Sprecher*innen oder Schreiber*innen eigentlich meinen. Dies erfordert eine Differenzierung in Gesagtes und Gemeintes. Doch diese Differenzierung ist längst nicht immer eindeutig und so lebt Ironie von einer interpretatorischen Ambivalenz, ob eine Äußerung wörtlich oder ironisch zu verstehen ist. Aufgrund dieser Ambivalenz und ihrer kulturgeschichtlichen Entwicklung erscheint Ironie als ebenso faszinierendes wie komplexes Sprach-Phänomen. Die vorliegende Einführung gibt aus kulturlinguistischer Perspektive Einblicke in die verschiedenen Möglichkeiten der theoretischen Beschreibung, methodischen Erfassung sowie empirischen Analyse von Ironie. Dabei werden einerseits alltagssprachliche Formen ironischen Kommunizierens in den Blick genommen, andererseits Möglichkeiten des interdisziplinären Anschlusses, um Ironie als linguistisches sowie als kulturgeschichtliches Phänomen zugänglich zu machen.

Das ‚andere‘ Europa der Schriftsteller. Ideen, Netzwerke und Schreibweisen des antiliberalen Europa-Diskurses in Deutschland und Österreich (1918–1934) - Heise, Tillmann

Reliable electrocortical dynamics of target-directed pass-kicks - Piskin, Daghan Yuksel; Büchel, Daniel; Lehmann, Tim; Baumeister, Jochen (Cognitive Neurodynamics)
Abstract Football is one of the most played sports in the world and kicking with adequate accuracy increases the likelihood of winning a competition. Although studies with different target-directed movements underline the role of distinctive cortical activity on superior accuracy, little is known about cortical dynamics associated with kicking. Mobile electroencephalography is a popular tool to investigate cortical modulations during movement, however, inherent and artefact-related pitfalls may obscure the reliability of functional sources and their activity. The purpose of this study was therefore to describe consistent cortical dynamics underlying target-directed pass-kicks based on test–retest reliability estimates. Eleven participants performed a target-directed kicking task at two different sessions within one week. Electroencephalography was recorded using a 65-channel mobile system and behavioural data were collected including motion range, acceleration and accuracy performance. Functional sources were identified using independent component analysis and clustered in two steps with the components of first and subsequently both sessions. Reliability estimates of event-related spectral perturbations were computed pixel-wise for participants contributing with components of both sessions. The parieto-occipital and frontal clusters were reproducible for the same majority of the sample at both sessions. Their activity showed consistent alpha desyhronization and theta sychnronisation patterns with substantial reliability estimates revealing visual and attentional demands in different phases of kicking. The findings of our study reveal prominent cortical demands during the execution of a target-directed kick which may be considered in practical implementations and provide promising academic prospects in the comprehension and investigation of cortical activity associated with target-directed movements.
Keywords: Exercise Neuroscience

§ 78 (Kartellrechtliche Grenzen der stillen Gesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

§ 6 (Kartellrechtliche Grenzen der Kommanditgesellschaft) - Bartlitz, David (Münchener Handbuch des Gesellschaftsrechts)

A large deformation gradient theory for glassy polymers by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (Archive of Applied Mechanics)
Abstract Cold forming of polycarbonate films results in the formation of shear bands in the necking zone. The numerical results obtained from standard viscoplastic material models exhibit mesh size dependency, requiring mathematical regularization. For this purpose, we present in this work a large deformation gradient theory for a viscoplastic isotropic material model published before. We extend our model to a micromorphic model by introducing a new micromorphic variable as an additional degree of freedom along with its first gradient. This variable represents a microequivalent plastic strain. The relation between the macroequivalent plastic strain and the micromorphic variable is accomplished by a micromorphic coupling modulus. This coupling forces proximity between the macro- and microvariables, leading to the targeted regularization effect. The micromorphic model is implemented as a three-dimensional initial boundary value problem in an in-house finite element tool. The analysis is performed for both uniaxial and biaxial specimens. The provided numerical examples show the ability of our model to regularize shear bands within the specimens and address the issue of localization.

DFT‐Assisted Investigation of the Electric Field and Charge Density Distribution of Pristine and Defective 2D WSe2 by Differential Phase Contrast Imaging - Groll, Maja; Bürger, Julius; Caltzidis, Ioannis; Jöns, Klaus D.; Schmidt, Wolf Gero; Gerstmann, Uwe; Lindner, Jörg K. N. (Small)
Abstract Most properties of solid materials are defined by their internal electric field and charge density distributions which so far are difficult to measure with high spatial resolution. Especially for 2D materials, the atomic electric fields influence the optoelectronic properties. In this study, the atomic‐scale electric field and charge density distribution of WSe 2 bi‐ and trilayers are revealed using an emerging microscopy technique, differential phase contrast (DPC) imaging in scanning transmission electron microscopy (STEM). For pristine material, a higher positive charge density located at the selenium atomic columns compared to the tungsten atomic columns is obtained and tentatively explained by a coherent scattering effect. Furthermore, the change in the electric field distribution induced by a missing selenium atomic column is investigated. A characteristic electric field distribution in the vicinity of the defect with locally reduced magnitudes compared to the pristine lattice is observed. This effect is accompanied by a considerable inward relaxation of the surrounding lattice, which according to first principles DFT calculation is fully compatible with a missing column of Se atoms. This shows that DPC imaging, as an electric field sensitive technique, provides additional and remarkable information to the otherwise only structural analysis obtained with conventional STEM imaging.

Analysis of Inverter Operation Modes of an IGBT-Based ZCS LLC Converter for a 2 kW Automotive On-Board DC-DC - Urbaneck, Daniel; Wiegard, Jan; Schafmeister, Frank (PCIM Europe 2024; IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

Natural near field coupled leaky-mode resonant anti-reflection structures: the setae of Cataglyphis bombycina - Schwind, Bertram; Wu, Xia; Tiemann, Michael; Fabritius, Helge-Otto (Frontiers in Physics)
Leaky mode resonances of the setae of Cataglyphis bombycina are found to enhance the thermal emission of the animals by near field coupling to the chitinous exoskeleton. This is remarkable, as the setae are also an adaption to enhance the reflectivity in the visible wavelength range. Both effects are dependent on morphology, dimensions and spatial arrangement. These parameters were experimentally characterized and simulated by finite difference time domain simulations to elucidate the optical impact of the setae in the mid infrared range and the contribution of leaky mode resonances. This mode of action and the setae’s optical properties in the visible range explain evolutionary strains that led to the actual morphology and size of the setae.

The acute effect of a β-glucan-enriched oat bread on gastric emptying, GLP-1 response, and postprandial glycaemia and insulinemia: a randomised crossover trial in healthy adults - Revheim, Ingrid; Ballance, Simon; Standal, Adelheid Fretland; Rieder, Anne; Dierkes, Jutta; Buyken, Anette; Gilja, Odd Helge; Hausken, Trygve; Rosendahl-Riise, Hanne (Nutrition & Metabolism)
Abstract Background The cereal fibre β-glucan reduces postprandial glycaemia, however, the underlying mechanisms are not fully understood. Thus, the aim of this study was to investigate the acute effect of a β-glucan-enriched oat bread on gastric emptying half-time ( T 1/2 ), gastric emptying lag phase ( T lag ), and gastric emptying rate (GER), and the secretion of glucagon-like peptide-1 (GLP-1) as potential means to influence postprandial glycaemia. Methods A randomised crossover trial was conducted in 22 healthy adults (age 24.6 ± 3.1 years, BMI 23.1 ± 2.7 kg/m 2 ) receiving 25 g available carbohydrates from a β-glucan-enriched oat bread or a control whole-wheat bread at two non-consecutive days. T 1/2 , T lag , and GER were determined based on ultrasound measures of the cross-sectional gastric antrum area in the fasting state and 15, 30, 45, 60, 90, and 120 min postprandially. Capillary glucose, serum insulin, and plasma GLP-1 concentrations were measured at the same time points. Results A biphasic pattern of gastric emptying with a distinct T lag before the commencement of emptying was observed in most subjects for both bread types. While no differences in GER were evident ( p = 0.562), consumption of the oat bread significantly increased T 1/2 by 18 min and T lag by 14 min compared with the whole-wheat bread ( p = 0.005 and p = 0.010, respectively). In addition, the oat bread significantly reduced iAUC 2h for glucose and insulin responses compared with the whole-wheat bread ( p = 0.001 and p < 0.001, respectively). There were no significant differences in GLP-1 response between the two breads ( p = 0.892). Conclusion The increased T 1/2 and T lag could offer a potential mechanism for the observed attenuation of postprandial glycaemia and insulinemia after consumption of the β-glucan-enriched oat bread compared with the whole-wheat bread. Trial registration : The study is registered at clinicaltrails.gov (NCT04571866).

Protein intake and cancer: an umbrella review of systematic reviews for the evidence-based guideline of the German Nutrition Society - Kühn, Tilman; Kalotai, Nicole; Amini, Anna M.; Haardt, Julia; Lehmann, Andreas; Schmidt, Annemarie; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Lorkowski, Stefan; Louis, Sandrine; et al. (European Journal of Nutrition)
Abstract Purpose It has been proposed that a higher habitual protein intake may increase cancer risk, possibly via upregulated insulin-like growth factor signalling. Since a systematic evaluation of human studies on protein intake and cancer risk based on a standardised assessment of systematic reviews (SRs) is lacking, we carried out an umbrella review of SRs on protein intake in relation to risks of different types of cancer. Methods Following a pre-specified protocol (PROSPERO: CRD42018082395), we retrieved SRs on protein intake and cancer risk published before January 22th 2024, and assessed the methodological quality and outcome-specific certainty of the evidence using a modified version of AMSTAR 2 and NutriGrade, respectively. The overall certainty of evidence was rated according to predefined criteria. Results Ten SRs were identified, of which eight included meta-analyses. Higher total protein intake was not associated with risks of breast, prostate, colorectal, ovarian, or pancreatic cancer incidence. The methodological quality of the included SRs ranged from critically low (kidney cancer), low (pancreatic, ovarian and prostate cancer) and moderate (breast and prostate cancer) to high (colorectal cancer). The outcome-specific certainty of the evidence underlying the reported findings on protein intake and cancer risk ranged from very low (pancreatic, ovarian and prostate cancer) to low (colorectal, ovarian, prostate, and breast cancer). Animal and plant protein intakes were not associated with cancer risks either at a low (breast and prostate cancer) or very low (pancreatic and prostate cancer) outcome-specific certainty of the evidence. Overall, the evidence for the lack of an association between protein intake and (i) colorectal cancer risk and (ii) breast cancer risk was rated as possible . By contrast, the evidence underlying the other reported results was rated as insufficient . Conclusion The present findings suggest that higher total protein intake may not be associated with the risk of colorectal and breast cancer, while conclusions on protein intake in relation to risks of other types of cancer are restricted due to insufficient evidence.

Dietary protein and blood pressure: an umbrella review of systematic reviews and evaluation of the evidence - Boeing, Heiner; Amini, Anna M.; Haardt, Julia; Schmidt, Annemarie; Bischoff-Ferrari, Heike A.; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Lorkowski, Stefan; Louis, Sandrine; Nimptsch, Katharina; et al. (European Journal of Nutrition)
Abstract Introduction This umbrella review aimed to investigate the evidence of an effect of dietary intake of total protein, animal and plant protein on blood pressure (BP), and hypertension (PROSPERO: CRD42018082395). Methods PubMed, Embase and Cochrane Database were systematically searched for systematic reviews (SRs) of prospective studies with or without meta-analysis published between 05/2007 and 10/2022. The methodological quality and outcome-specific certainty of evidence were assessed by the AMSTAR 2 and NutriGrade tools, followed by an assessment of the overall certainty of evidence. SRs investigating specific protein sources are described in this review, but not included in the assessment of the overall certainty of evidence. Results Sixteen SRs were considered eligible for the umbrella review. Ten of the SRs investigated total protein intake, six animal protein, six plant protein and four animal vs. plant protein. The majority of the SRs reported no associations or effects of total, animal and plant protein on BP (all “possible” evidence), whereby the uncertainty regarding the effects on BP was particularly high for plant protein. Two SRs addressing milk-derived protein showed a reduction in BP; in contrast, SRs investigating soy protein found no effect on BP. The outcome-specific certainty of evidence of the SRs was mostly rated as low. Discussion/conclusion This umbrella review showed uncertainties whether there are any effects on BP from the intake of total protein, or animal or plant proteins, specifically. Based on data from two SRs with milk protein, it cannot be excluded that certain types of protein could favourably influence BP.

Glycemic response to meals with a high glycemic index differs between morning and evening: a randomized cross-over controlled trial among students with early or late chronotype - Stutz, Bianca; Krueger, Bettina; Goletzke, Janina; Jankovic, Nicole; Alexy, Ute; Herder, Christian; Dierkes, Jutta; Berg-Beckhoff, Gabriele; Jakobsmeyer, Rasmus; Reinsberger, Claus; Buyken, Anette (European Journal of Nutrition)
Abstract Purpose Glycemic response to the same meal depends on daytime and alignment of consumption with the inner clock, which has not been examined by individual chronotype yet. This study examined whether the 2-h postprandial and 24-h glycemic response to a meal with high glycemic index (GI) differ when consumed early or late in the day among students with early or late chronotype. Methods From a screening of 327 students aged 18–25 years, those with early (n = 22) or late (n = 23) chronotype participated in a 7-day randomized controlled cross-over intervention study. After a 3-day observational phase, standardized meals were provided on run-in/washout (days 4 and 6) and intervention (days 5 and 7), on which participants received a high GI meal (GI = 72) in the morning (7 a.m.) or in the evening (8 p.m.). All other meals had a medium GI. Continuous glucose monitoring was used to measure 2-h postprandial and 24-h glycemic responses and their variability. Results Among students with early chronotype 2-h postprandial glucose responses to the high GI meal were higher in the evening than in the morning (iAUC: 234 (± 92) vs. 195 (± 91) (mmol/L) × min, p = 0.042). Likewise, mean and lowest 2-h postprandial glucose values were higher when the high GI meal was consumed in the evening (p < 0.001; p = 0.017). 24-h glycemic responses were similar irrespective of meal time. Participants with late chronotype consuming a high GI meal in the morning or evening showed similar 2-h postprandial (iAUC: 211 (± 110) vs. 207 (± 95) (mmol/L) × min, p = 0.9) and 24-h glycemic responses at both daytimes. Conclusions Diurnal differences in response to a high GI meal are confined to those young adults with early chronotype, whilst those with a late chronotype seem vulnerable to both very early and late high GI meals. Registered at clinicaltrials.gov (NCT04298645; 22/01/2020).

Architektur der Bildungsoffensive. Die NRW-Gesamthochschulen - Seng, Eva- Maria (Junge Hochschulen“ – wissenschafts- und hochschulpolitische Herausforderungen seit der 2. Hälfte des 20. Jahrhunderts)

Utilizing Description Logics for Global Explanations of Heterogeneous Graph Neural Networks - Köhler, Dominik; Heindorf, Stefan (arXiv:2405.12654)
Graph Neural Networks (GNNs) are effective for node classification in graph-structured data, but they lack explainability, especially at the global level. Current research mainly utilizes subgraphs of the input as local explanations or generates new graphs as global explanations. However, these graph-based methods are limited in their ability to explain classes with multiple sufficient explanations. To provide more expressive explanations, we propose utilizing class expressions (CEs) from the field of description logic (DL). Our approach explains heterogeneous graphs with different types of nodes using CEs in the EL description logic. To identify the best explanation among multiple candidate explanations, we employ and compare two different scoring functions: (1) For a given CE, we construct multiple graphs, have the GNN make a prediction for each graph, and aggregate the predicted scores. (2) We score the CE in terms of fidelity, i.e., we compare the predictions of the GNN to the predictions by the CE on a separate validation set. Instead of subgraph-based explanations, we offer CE-based explanations.

AFM-IR investigation of thin PECVD SiOx films on a polypropylene substrate in the surface-sensitive mode - Müller, Hendrik; Stadler, Hartmut; de los Arcos, Teresa; Keller, Adrian; Grundmeier, Guido (Beilstein Journal of Nanotechnology)
Thin silicon oxide films deposited on a polypropylene substrate by plasma-enhanced chemical vapor deposition were investigated using atomic force microscopy-based infrared (AFM-IR) nanospectroscopy in contact and surface-sensitive mode. The focus of this work is the comparison of the different measurement methods (i.e., contact mode and surface-sensitive mode) with respect to the chemical surface sensitivity. The use of the surface-sensitive mode in AFM-IR shows an enormous improvement for the analysis of thin films on the IR-active substrate. As a result, in this mode, the signal of the substrate material could be significantly reduced. Even layers that are so thin that they could hardly be measured in the contact mode can be analyzed with the surface-sensitive mode.

Stimuli‐accelerated polymeric drug delivery systems - Rust, Tarik; Jung, Dimitri; Langer, Klaus; Kuckling, Dirk (Polymer International)
The controlled delivery of active pharmaceutical ingredients to the site of disease represents a major challenge in drug therapy. Particularly when drugs have to be transported across biological barriers, suitable drug delivery systems are of importance. In recent years responsive delivery systems have been developed which enable a controlled drug release depending on internal or external stimuli such as changes in pH, redox environment or light and temperature. In some studies delivery systems with reactivity against two different stimuli were established either to enhance the response by synergies of the stimuli or to broaden the window of possible trigger events. In the present review numerous exciting developments of pH-, light- and redox-cleavable polymers suitable for the preparation of smart delivery systems are described. The review discusses the different stimuli that can be used for a controlled drug release of polymer-based delivery systems. It puts a focus on the different polymers described for the preparation of stimuli-sensitive systems, their preparation techniques as well as their stimuli-responsive degradation. © 2022 The Authors. Polymer International published by John Wiley & Sons Ltd on behalf of Society of Industrial Chemistry.
Keywords: drug delivery system; stimuli; polymer; cleavable

Zu unangenehm, zu viel Aufwand oder keine Möglichkeit? – Emotionen und Bereitschaft von Lehramtsstudierenden zur Videografie eigenen Unterrichts - Vogelsang, Christoph; Pollmeier, Pascal; Gockeln, Theresa; Rogge, Tim (Zeitschrift für Bildungsforschung)
Videografien eigenen Unterrichts sind ein mögliches methodisches Werkzeug zur Förderung der professionellen Kompetenz angehender Lehrkräfte, das allerdings innerhalb der Lehramtsausbildung noch nicht breit implementiert ist. Ein möglicher Grund hierfür könnte neben organisatorischen Herausforderungen auch in einer geringen Akzeptanz von Eigenvideografien durch Lehramtsstudierende liegen. Um besser abschätzen zu können, mit welchen Voraussetzungen affektiv-emotionaler Art bei einer breiteren Implementierung im Lehramtsstudium gerechnet werden kann, wurden N = 938 Lehramtsstudierende im Masterstudium an der Universität Paderborn zu ihren Emotionen und Bereitschaften zur Arbeit mit Eigenvideografien befragt. Dabei wurde auch erfasst, wie sich diese je nach bestehenden Erfahrungen zur Arbeit mit Videografien unterscheiden. In den Ergebnissen zeigen sich kaum affektiv-emotionale Reaktionen zur Eigenvideografie, und wenn, vor allem Gefühle der Unsicherheit. Zu beachten ist, dass zwar bei gut der Hälfte der Studierenden eine eher hohe generelle Bereitschaft zur Eigenvideografie besteht, eine konkrete Intention bzw. eine konkrete Volition zur Videografie aber geringer ist. Die ca. 10 % der Studierenden mit Eigenvideografieerfahrung im Studium zeigen erwartungsgemäß höhere Bereitschaften, aber unerwartet keine signifikant positiveren Emotionen. Insgesamt verdeutlichen die Ergebnisse, dass bzgl. der Akzeptanz der Studierenden ein höheres Potenzial zur Implementation von Eigenvideografien im Studium vorliegt, als aktuell ausgeschöpft wird.
Keywords: Lehrerbildung; Videografie; Praxissemester; Emotionen; Akzeptanz

Responses to heat waves: what can Twitter data tell us? - Zander, Kerstin K.; Rieskamp, Jonas; Mirbabaie, Milad; Alazab, Mamoun; Nguyen, Duy (Natural Hazards)
Abstract Increasing average temperatures and heat waves are having devasting impacts on human health and well-being but studies of heat impacts and how people adapt are rare and often confined to specific locations. In this study, we explore how analysis of conversations on social media can be used to understand how people feel about heat waves and how they respond. We collected global Twitter data over four months (from January to April 2022) using predefined hashtags about heat waves. Topic modelling identified five topics. The largest (one-third of all tweets) was related to sports events. The remaining two-thirds could be allocated to four topics connected to communication about climate-related heat or heat waves. Two of these were on the impacts of heat and heat waves (health impacts 20%; social impacts 16%), one was on extreme weather and climate change attribution (17%) and the last one was on perceptions and warning (13%). The number of tweets in each week corresponded well with major heat wave occurrences in Argentina, Australia, the USA and South Asia (India and Pakistan), indicating that people posting tweets were aware of the threat from heat and its impacts on the society. Among the words frequently used within the topic ‘Social impacts’ were ‘air-conditioning’ and ‘electricity’, suggesting links between coping strategies and financial pressure. Apart from analysing the content of tweets, new insights were also obtained from analysing how people engaged with Twitter tweets about heat or heat waves. We found that tweets posted early, and which were then shared by other influential Twitter users, were among the most popular. Finally, we found that the most popular tweets belonged to individual scientists or respected news outlets, with no evidence that misinformation about climate change-related heat is widespread.
Keywords: Earth and Planetary Sciences (miscellaneous); Atmospheric Science; Water Science and Technology

Dynamics of DNA Origami Lattices - Julin, Sofia; Keller, Adrian; Linko, Veikko (Bioconjugate Chemistry)
Keywords: Organic Chemistry; Pharmaceutical Science; Pharmacology; Biomedical Engineering; Bioengineering; Biotechnology

Does Augmented Reality Help to Understand Chemical Phenomena during Hands-On Experiments?–Implications for Cognitive Load and Learning - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Multimodal Technologies and Interaction)
Chemical phenomena are only observable on a macroscopic level, whereas they are explained by entities on a non-visible level. Students often demonstrate limited ability to link these different levels. Augmented reality (AR) offers the possibility to increase contiguity by embedding virtual models into hands-on experiments. Therefore, this paper presents a pre- and post-test study investigating how learning and cognitive load are influenced by AR during hands-on experiments. Three comparison groups (AR, animation and filmstrip), with a total of N = 104 German secondary school students, conducted and explained two hands-on experiments. Whereas the AR group was allowed to use an AR app showing virtual models of the processes on the submicroscopic level during the experiments, the two other groups were provided with the same dynamic or static models after experimenting. Results indicate no significant learning gain for the AR group in contrast to the two other groups. The perceived intrinsic cognitive load was higher for the AR group in both experiments as well as the extraneous load in the second experiment. It can be concluded that AR could not unleash its theoretically derived potential in the present study.
Keywords: augmented reality; chemistry education; models; experiment; cognitive load

Reusability of Germany´s total diet study food list upon availability of new food consumption data—comparison of three update strategies - Kolbaum, Anna Elena; Ptok, Sebastian; Jung, Christian; Libuda, Lars; Lindtner, Oliver (Journal of Exposure Science & Environmental Epidemiology)
Abstract Background The German total diet study (TDS)—BfR MEAL Study—established its food list in 2016 based on food consumption data of children (0.5–<5 years) and adults (14–80 years). The list consists of 356 foods selected for analysis in order to ensure ≥90% coverage of the diet. Recently, new food consumption data for children (0.5–<6 and 6–<12 years) in Germany became available, which raised the opportunity to evaluate the applicability of the MEAL food list 2016 on new data. Objective We tested the hypotheses that the MEAL food list 2016 also covers ≥90% of the diet of the new collected food consumption data, and that the selection of foods from younger children and adults was sufficient to also cover the middle age group (6–<12 years). Strategies for updating the existing food list were assessed. Methods Three approaches evaluated the reusability and potential adjustment strategies of the existing food list. Approach 1 applied the existing food list to new food consumption data. Approach 2 allowed the extension of the existing food list to improve coverage of food consumption. Approach 3 set up a new food list based on the new data. Results The MEAL food list 2016 covered 94% of the overall diet of the new collected food consumption data. The diet of the middle age group was sufficiently covered with 91%. However, coverage on main food group or population subgroup level was <90% in some cases. Approach 3 most accurately identified relevant modifications to the existing food list. 94% of the MEAL food list 2016 could be re-used and 51 new foods were identified as potentially relevant. Significance The results suggest that a high investment in the coverage of a TDS food list will lower the effort and the resources to keep data updated in the long-term. Impact There is no established approach to update a TDS food list. This study provides comparative approaches to handle newly collected food consumption data for follow-on TDS activities. The results provide useful information for institutions planning or updating a TDS. Furthermore, new food consumption data for children in Germany recently became available and are here presented for the first time.
Keywords: Public Health; Environmental and Occupational Health; Pollution; Toxicology; Epidemiology

Quantum space, ground space traversal, and how to embed multi-prover interactive proofs into unentanglement - Gharibian, Sevag; Rudolph, Dorian (14th Innovations in Theoretical Computer Science (ITCS))
Savitch's theorem states that NPSPACE computations can be simulated in PSPACE. We initiate the study of a quantum analogue of NPSPACE, denoted Streaming-QCMASPACE (SQCMASPACE), where an exponentially long classical proof is streamed to a poly-space quantum verifier. Besides two main results, we also show that a quantum analogue of Savitch's theorem is unlikely to hold, as SQCMASPACE=NEXP. For completeness, we introduce Streaming-QMASPACE (SQMASPACE) with an exponentially long streamed quantum proof, and show SQMASPACE=QMA_EXP (quantum analogue of NEXP). Our first main result shows, in contrast to the classical setting, the solution space of a quantum constraint satisfaction problem (i.e. a local Hamiltonian) is always connected when exponentially long proofs are permitted. For this, we show how to simulate any Lipschitz continuous path on the unit hypersphere via a sequence of local unitary gates, at the expense of blowing up the circuit size. This shows quantum error-correcting codes can be unable to detect one codeword erroneously evolving to another if the evolution happens sufficiently slowly, and answers an open question of [Gharibian, Sikora, ICALP 2015] regarding the Ground State Connectivity problem. Our second main result is that any SQCMASPACE computation can be embedded into "unentanglement", i.e. into a quantum constraint satisfaction problem with unentangled provers. Formally, we show how to embed SQCMASPACE into the Sparse Separable Hamiltonian problem of [Chailloux, Sattath, CCC 2012] (QMA(2)-complete for 1/poly promise gap), at the expense of scaling the promise gap with the streamed proof size. As a corollary, we obtain the first systematic construction for obtaining QMA(2)-type upper bounds on arbitrary multi-prover interactive proof systems, where the QMA(2) promise gap scales exponentially with the number of bits of communication in the interactive proof.

On the structure of regularization paths for piecewise differentiable regularization terms - Gebken, Bennet; Bieker, Katharina; Peitz, Sebastian (Journal of Global Optimization)
Regularization is used in many different areas of optimization when solutions are sought which not only minimize a given function, but also possess a certain degree of regularity. Popular applications are image denoising, sparse regression and machine learning. Since the choice of the regularization parameter is crucial but often difficult, path-following methods are used to approximate the entire regularization path, i.e., the set of all possible solutions for all regularization parameters. Due to their nature, the development of these methods requires structural results about the regularization path. The goal of this article is to derive these results for the case of a smooth objective function which is penalized by a piecewise differentiable regularization term. We do this by treating regularization as a multiobjective optimization problem. Our results suggest that even in this general case, the regularization path is piecewise smooth. Moreover, our theory allows for a classification of the nonsmooth features that occur in between smooth parts. This is demonstrated in two applications, namely support-vector machines and exact penalty methods.

Zur Effektivität des europäischen Kronzeugenprogramms - Der Fall des LKW-Kartells - Tiessen, Michelle

Characterizing Ion Transport in Electrolytes via Concentration and Velocity Profiles - Mistry, Aashutosh; Srinivasan, Venkat; Steinrück, Hans-Georg (Advanced Energy Materials)
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment

Beep-and-Sleep: Message and Energy Efficient Set Cover - Götte, Thorsten; Kolb, Christina; Scheideler, Christian; Werthmann, Julian (Theor. Comput. Sci.)

Digitalität, Mediatisierung und Bildung - Megatrends aus medienpädagogischer Perspektive - Herzig, Bardo (Bildung und Digitalität. Analysen - Diskurse - Perspektiven)

Narratives and Mental Health: An Introduction - Mildorf, Jarmila; Punzi, Elisabeth; Singer, Christoph (Narrative and Mental Health: Reimagining Theory and Practice)

Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C−F and S−F Bond Activation - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C−F and S−F Bond Activation - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan (Angewandte Chemie)
Keywords: General Medicine

Experimental and simulative determination and correction of the effective gap extension in structured coaxial measuring systems - Josch, Sebastian; Jesinghausen, Steffen; Dechert, Christopher; Schmid, Hans-Joachim (Rheologica Acta)
Abstract The use of structured measuring systems to prevent wall slip is a common approach to obtain absolute rheological values. Typically, only the minimum distance between the measuring surfaces is used for further calculation, implying that no flow occurs between the structural elements. But this assumption is misleading, and a gap correction is necessary. To determine the radius correction $$Δ r$$ Δ r for specific geometries, we conducted investigations on three Newtonian fluids (two silicon oils and one suspension considered to be Newtonian in the relevant shear rate range). The results show that $$Δ r$$ Δ r is not only shear- and material-independent, but geometry-dependent, providing a Newtonian flow behaviour in a similar viscosity range. Therefore, a correction value can be determined with only minute deviations in different Newtonian fluids. As the conducted laboratory measurements are very time-consuming and expensive, a CFD-approach with only very small deviations was additionally developed and compared for validation purposes. Therefore, simulation is an effective and resource-efficient alternative to the presented laboratory measurements to determine $$Δ r$$ Δ r for the correction of structured coaxial geometries even for non-Newtonian fluids in the future.
Keywords: rheology; rheometry; suspension; coaxial; correction

Correction: Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koshukow, Wikentij; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert

Who benefits from quality competition in health care? A theory and a laboratory experiment on the relevance of patient characteristics - Brosig-Koch, Jeannette; Hehenkamp, Burkhard; Kokot, Johanna (Health Economics)
We study how competition between physicians affects the provision of medical care. In our theoretical model, physicians are faced with a heterogeneous patient population, in which patients systematically vary with regard to both their responsiveness to the provided quality of care and their state of health. We test the behavioral predictions derived from this model in a controlled laboratory experiment. In line with the model, we observe that competition significantly improves patient benefits as long as patients are able to respond to the quality provided. For those patients, who are not able to choose a physician, competition even decreases the patient benefit compared to a situation without competition. This decrease is in contrast to our theoretical prediction implying no change in benefits for passive patients. Deviations from patient-optimal treatment are highest for passive patients in need of a low quantity of medical services. With repetition, both, the positive effects of competition for active patients as well as the negative effects of competition for passive patients become more pronounced. Our results imply that competition can not only improve but also worsen patient outcome and that patients’ responsiveness to quality is decisive.
Keywords: physician competition; patient characteristics; heterogeneity in quality responses; fee-for-service; laboratory experiment

Price Regulation, Quality Competition and Location Choice with Costly Relocation - Hehenkamp, Burkhard; Kaarbøe, Oddvar M.
We consider a model where for-profit providers compete in quality in a price-regulated market that has been opened to competition, and where the incumbent is located at the center of the market, facing high costs of relocation. The model is relevant in markets such as public health care, education and schooling, or postal services. We find that, when the regulated price is low or intermediate, the entrant strategically locates towards the corner of the market to keep the incumbent at the low monopoly quality level. For a high price, the entrant locates at the corner of the market and both providers implement higher quality compared to a monopoly. In any case, the entrant implements higher quality than the incumbent provider. Social welfare is always higher in a duopoly if the cost of quality is low. For higher cost levels welfare is non-monotonic in the price and it can be optimal to the regulator not to use its entire budget. Therefore, the welfare effect of entry depends on the price and the size of the entry cost, and the regulator should condition the decision to allow entry on an assessment of the entry cost.
Keywords: Quality competition; Price regulation; Location choice; Product differentiation

A multi-mode super-fano mechanism for enhanced third harmonic generation in silicon metasurfaces - Hähnel, David; Golla, Christian; Albert, Maximilian; Zentgraf, Thomas; Myroshnychenko, Viktor; Förstner, Jens; Meier, Cedrik (Light: Science & Applications)
We present strong enhancement of third harmonic generation in an amorphous silicon metasurface consisting of elliptical nano resonators. We show that this enhancement originates from a new type of multi-mode Fano mechanism. These ‘Super-Fano’ resonances are investigated numerically in great detail using full-wave simulations. The theoretically predicted behavior of the metasurface is experimentally verified by linear and nonlinear transmission spectroscopy. Moreover, quantitative nonlinear measurements are performed, in which an absolute conversion efficiency as high as ηmax ≈ 2.8 × 10−7 a peak power intensity of 1.2 GW cm−2 is found. Compared to an unpatterned silicon film of the same thickness amplification factors of up to ~900 are demonstrated. Our results pave the way to exploiting a strong Fano-type multi-mode coupling in metasurfaces for high THG in potential applications.
Keywords: tet_topic_meta

Morphological and mechanical properties of foamed thick-walled Wood-Plastic-Composite structures - Moritzer, Elmar; Flachmann, Felix (Journal of Cellular Plastics)
Microcellular wood fiber reinforced polymers offer the possibility to reduce the use of fossil raw materials. In particular, thick-walled structures with thicknesses greater than 6 mm offer a high potential for weight savings. This study investigates the cell structures and mechanical properties of injection-molded test specimens. The influence of different thicknesses (6–10 mm) along with different chemical blowing agents (endothermic, exothermic) with varying dosages (0–2 wt%) is analyzed. The investigations reveal that exothermic chemical blowing agents form finer cells consistently to thin-walled structures than endothermic ones. Higher foaming agent content leads to higher pore fractions, with many small cells coalescing into a large open-pore cell network. The mechanical properties depend mainly on the pore content of the sample. The specific tensile properties deteriorate with the use of chemical blowing agents (CFA), whereas the sandwich structure produced with compact edge layers has a positive influence on the specific flexural properties.
Keywords: Materials Chemistry; Polymers and Plastics; General Chemistry

Thermal conductivity of solid paraffins and several n-docosane compounds with graphite - Paul, Andreas; Baumhögger, Elmar; Dewerth, Mats-Ole; Hami Dindar, Iman; Sonnenrein, Gerrit; Vrabec, Jadran (Journal of Thermal Analysis and Calorimetry)
The technical importance of paraffins as phase change materials (PCM) in heat storage systems increases. Knowledge on the thermal conductivity of paraffins is necessary for the design and optimization of heat storage systems. However, for most paraffins solely the thermal conductivity of the liquid state has been sufficiently investigated. For the solid state, precise thermal conductivity data are only known for a few paraffins, while only generalized values are available for the remainder, some of which contradict each other. In this study, a measurement setup based on the modified guarded hot plate method is developed. It is used to investigate the thermal conductivity of several paraffines in the solid state, including pure n-docosane and its compounds with different types and concentrations of graphite. For n-docosane in the solid state, the thermal conductivity is determined to be 0.49 W/(m K). A particle size of 200 μm with a spherical shape turns out to be optimal to increase the thermal conductivity. This allows the thermal conductivity of a compound with 10% graphite to increase by a factor of three compared to the pure paraffin. Furthermore, significant differences to thermal conductivity data from the literature are found.
Keywords: Physical and Theoretical Chemistry; Condensed Matter Physics

Selective Discrimination between CO and H2 with Copper–Ceria-Resistive Gas Sensors - Baier, Dominik; Priamushko, Tatiana; Weinberger, Christian; Kleitz, Freddy; Tiemann, Michael (ACS Sensors)
The production of hydrogen and the utilization of biomass for sustainable concepts of energy conversion and storage require gas sensors that discriminate between hydrogen (H2) and carbon monoxide (CO). Mesoporous copper–ceria (Cu–CeO2) materials with large specific surface areas and uniform porosity are prepared by nanocasting, and their textural properties are characterized by N2 physisorption, powder XRD, scanning electron microscopy, transmission electron microscopy, and energy-dispersive X-ray spectroscopy. The oxidation states of copper (Cu+, Cu2+) and cerium (Ce3+, Ce4+) are investigated by XPS. The materials are used as resistive gas sensors for H2 and CO. The sensors show a stronger response to CO than to H2 and low cross-sensitivity to humidity. Copper turns out to be a necessary component; copper-free ceria materials prepared by the same method show only poor sensing performance. By measuring both gases (CO and H2) simultaneously, it is shown that this behavior can be utilized for selective sensing of CO in the presence of H2.
Keywords: Fluid Flow and Transfer Processes; Process Chemistry and Technology; Instrumentation; Bioengineering

Proof of concept for incremental sheet metal forming by means of electromagnetic and electrohydraulic high-speed forming - Holzmüller, Maik; Linnemann, Maik; Homberg, Werner; Psyk, Verena; Kräusel, Verena; Kroos, Janika (Materials Research Proceedings)
Abstract. The combination of incremental sheet metal forming and high-speed forming offers new possibilities for flexible forming processes in the production of large sheet metal components of increased complexity with relatively low forming energies. In this paper, the general feasibility and process differences between the pulse-driven high-speed forming technologies of electrohydraulic and electromagnetic forming were investigated. An example component made of EN AW 6016 aluminum sheet metal was thus formed incrementally by both processes and the forming result evaluated by an optical 3D measurement system. For this purpose, a forming strategy for electromagnetic incremental forming (EMIF) was developed, tested and adapted to the electrohydraulic incremental forming process (EHIF). The discharge energy, the tool displacement and the pressure field of the forming zone were determined as relevant parameters for the definition of an adequate tool path strategy. It was found that the EHIF process is less affected by larger distances between the tool and the blank, while this is a critical variable for force application to the component during EMIF. On the other hand, the more uniform pressure distribution of the EMIF process is advantageous for forming large steady component areas.
Keywords: Incremental Sheet Forming; Aluminium; High-Speed Forming

Understanding the Redox Mechanism of Sulfurized Poly(acrylonitrile) as Highly Rate and Cycle Stable Cathode Material for Sodium-Sulfur Batteries - Kappler, Julian; Tonbul, Güldeniz; Schoch, Roland; Murugan, Saravanakumar; Nowakowski, Michał; Lange, Pia Lena; Klostermann, Sina Vanessa; Bauer, Matthias; Schleid, Thomas; Kästner, Johannes; Buchmeiser, Michael Rudolf (Journal of The Electrochemical Society)
Room temperature sodium-sulfur (RT Na-S) batteries are considered potential candidates for stationary power storage applications due to their low cost, broad active material availability and low toxicity. Challenges, such as high volume expansion of the S-cathode upon discharge, low electronic conductivity of S as active material and herewith limited rate capability as well as the shuttling of polysulfides (PSs) as intermediates often impede the cycle stability and practical application of Na-S batteries. Sulfurized poly(acrylonitrile) (SPAN) inherently inhibits the shuttling of PSs and shows compatibility with carbonate-based electrolytes, however, its exact redox mechanism remained unclear to date. Herein, we implement a commercially available and simple electrolyte into the Na-SPAN cell chemistry and demonstrate its high rate and cycle stability. Through the application of in situ techniques utilizing electronic impedance spectroscopy (EIS) and X-ray absorption spectroscopy (XAS) at different depths of charge and discharge, an insight into SPAN’s redox chemistry is obtained.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Characterization of Na-S Battery System Using X-ray Absorption Spectroscopy - Tonbul, Güldeniz; Kappler, Julian; Murugan, Saravanakumar; Schoch, Roland; Nowakowski, Michal; Lange, Pia; Bauer, Matthias; Buchmeiser, Michael R.

Musiklandschaften zwischen Rhein und Weser – Einführung - Meine, Sabine; Otto, Arnold; Süßmann, Johannes (Musiklandschaften zwischen Rhein und Weser. Pluralisierung und Verflechtung entlang des Hellwegs in der Frühen Neuzeit. Unter Mitarbeit v. Markus Lauert)

Large-Scale Formation of DNA Origami Lattices on Silicon - Tapio, Kosti; Kielar, Charlotte; Parikka, Johannes M.; Keller, Adrian; Järvinen, Heini; Fahmy, Karim; Toppari, J. Jussi (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Nanoparticle‐Based Formulations of Glycopeptide Antibiotics: A Means for Overcoming Vancomycin Resistance in Bacterial Pathogens? - Pothineni, Bhanu Kiran; Keller, Adrian (Advanced NanoBiomed Research)
Keywords: General Medicine

Effect of Ionic Strength on the Thermal Stability of DNA Origami Nanostructures - Hanke, Marcel; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

Stability of DNA Origami Nanostructures in Physiological Media: The Role of Molecular Interactions - Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Detecting Novelties with Empty Classes - Uhlemeyer, Svenja; Lienen, Julian; Hüllermeier, Eyke; Gottschalk, Hanno (arXiv:2305.00983)
For open world applications, deep neural networks (DNNs) need to be aware of previously unseen data and adaptable to evolving environments. Furthermore, it is desirable to detect and learn novel classes which are not included in the DNNs underlying set of semantic classes in an unsupervised fashion. The method proposed in this article builds upon anomaly detection to retrieve out-of-distribution (OoD) data as candidates for new classes. We thereafter extend the DNN by $k$ empty classes and fine-tune it on the OoD data samples. To this end, we introduce two loss functions, which 1) entice the DNN to assign OoD samples to the empty classes and 2) to minimize the inner-class feature distances between them. Thus, instead of ground truth which contains labels for the different novel classes, the DNN obtains a single OoD label together with a distance matrix, which is computed in advance. We perform several experiments for image classification and semantic segmentation, which demonstrate that a DNN can extend its own semantic space by multiple classes without having access to ground truth.

Structure–Reactivity Relationships in Borane-Based FLP-Catalyzed Hydrogenations, Dehydrogenations, and Cycloisomerizations - Paradies, Jan (Accounts of Chemical Research)
Keywords: General Medicine; General Chemistry

Exergaming in older adults: the effects of game characteristics on brain activity and physical activity - Müller, Helen; Baumeister, Jochen; Bardal, Ellen Marie; Vereijken, Beatrix; Skjæret-Maroni, Nina (Frontiers in Aging Neuroscience)
Introduction Exergames are increasingly used in rehabilitation settings for older adults to train physical and cognitive abilities. To meet the potential that exergames hold, they need to be adapted to the individual abilities of the player and their training objectives. Therefore, it is important to know whether and how game characteristics affect their playing. The aim of this study is to investigate the effect of two different kinds of exergame (step game and balance game) played at two difficulty levels on brain activity and physical activity. Methods Twenty-eight older independently living adults played two different exergames at two difficulty levels each. In addition, the same movements as during gaming (leaning sideways with feet in place and stepping sideways) were performed as reference movements. Brain activity was recorded using a 64-channel EEG system to assess brain activity, while physical activity was recorded using an accelerometer at the lower back and a heart rate sensor. Source-space analysis was applied to analyze the power spectral density in theta (4 Hz–7 Hz) and alpha-2 (10 Hz–12 Hz) frequency bands. Vector magnitude was applied to the acceleration data. Results Friedman ANOVA revealed significantly higher theta power for the exergaming conditions compared to the reference movement for both games. Alpha-2 power showed a more diverse pattern which might be attributed to task-specific conditions. Acceleration decreased significantly from the reference movement to the easy condition to the hard condition for both games. Discussion The results indicate that exergaming increases frontal theta activity irrespective of type of game or difficulty level, while physical activity decreases with increasing difficulty level. Heart rate was found to be an inappropriate measure in this population older adults. These findings contribute to understanding of how game characteristics affect physical and cognitive activity and consequently need to be taken into account when choosing appropriate games and game settings for exergame interventions.
Keywords: Cognitive Neuroscience; Aging

Minimum Edge Cuts in Overlay Networks - Schweichhart, Jonas

Hard carbon microspheres with bimodal size distribution and hierarchical porosity via hydrothermal carbonization of trehalose - Wortmann, Martin; Keil, Waldemar; Diestelhorst, Elise; Westphal, Michael; Haverkamp, René; Brockhagen, Bennet; Biedinger, Jan; Bondzio, Laila; Weinberger, Christian; Baier, Dominik; Tiemann, Michael; Hütten, Andreas; et al. (RSC Advances)
Hydrothermal carbonization (HTC) is an efficient thermochemical method for the conversion of organic feedstock to carbonaceous solids. HTC of different saccharides is known to produce microspheres (MS) with mostly Gaussian size distribution, which are utilized as functional materials in various applications, both as pristine MS and as a precursor for hard carbon MS. Although the average size of the MS can be influenced by adjusting the process parameters, there is no reliable mechanism to affect their size distribution. Our results demonstrate that HTC of trehalose, in contrast to other saccharides, results in a distinctly bimodal sphere diameter distribution consisting of small spheres with diameters of (2.1 ± 0.2) μm and of large spheres with diameters of (10.4 ± 2.6) μm. Remarkably, after pyrolytic post-carbonization at 1000 °C the MS develop a multimodal pore size distribution with abundant macropores > 100 nm, mesopores > 10 nm and micropores < 2 nm, which were examined by small-angle X-ray scattering and visualized by charge-compensated helium ion microscopy. The bimodal size distribution and hierarchical porosity provide an extraordinary set of properties and potential variables for the tailored synthesis of hierarchical porous carbons, making trehalose-derived hard carbon MS a highly promising material for applications in catalysis, filtration, and energy storage devices.
Keywords: General Chemical Engineering; General Chemistry

Model-driven Collaborative Design of Professional Education Programmes With Extended Online Whiteboards - Wolters, Dennis; Engels, Gregor (MODELSWARD'23)

Ratings Meet Prices: The Dynamic Relationship of Quality Signals - Kaimann, Daniel; Spiess Bru, Clarissa Laura Maria; Frick, Bernd (Journal of Wine Economics)

Ultrafast Proton Transfer Pathways Mediated by Amphoteric Imidazole - Codescu, M.-A.; Kunze, T.; Weiß, M.; Brehm, Martin; Kornilov, O.; Sebastiani, D.; Nibbering, E. T. J. (J. Phys. Chem. Lett.)

A Force Field for Bio-Polymers in Ionic Liquids (BILFF) – Part 2: Cellulose in [EMIm][OAc] / Water Mixtures - Roos, E.; Sebastiani, D.; Brehm, Martin (Phys. Chem. Chem. Phys.)

Lactate-Based Ionic Liquids as Chiral Solvents for Cellulose - Radicke, J.; Roos, E.; Sebastiani, D.; Brehm, Martin; Kressler, J. (J. Polym. Sci.)